Synthesis and evaluation of new 2-aminothiophenes against Mycobacterium tuberculosis. Issue 25 (2nd June 2016) - Thanna, Sandeep; Knudson, Susan E.; Grzegorzewicz, Anna; Kapil, Sunayana; Goins, Christopher M.; Ronning, Donald R.; Jackson, Mary; Slayden, Richard A.; Sucheck, Steven J.
Abstract : New 2-aminothiophenes (2AT) were identified with MICs = 0.23–0.44 μM against drug sensitive and drug resistant strains of Mycobacterium tuberculosis . Abstract : Tuberculosis (TB) and its drug resistant forms kills more people than any other infectious disease. This fact emphasizes the need to identify new drugs to treat TB. 2-Aminothiophenes (2AT) have been reported to inhibit Pks13, a validated anti-TB drug target. We synthesized a library of 42 2AT compounds. Among these, compound33 showed remarkable potency against Mycobacterium tuberculosis ( Mtb ) H37RV (MIC = 0.23 μM) and showed an impressive potency (MIC = 0.20–0.44 μM) against Mtb strains resistant to isoniazid, rifampicin and fluoroquinolones. The site of action for the compound33 is presumed to be Pks13 or an earlier enzyme in the mycolic acid biosynthetic pathway. This inference is based on structural similarity of the compound33 with known Pks13 inhibitors, which is corroborated by mycolic acid biosynthesis studies showing that the compound strongly inhibits the biosynthesis of all forms of mycolic acid in Mtb . In summary, these studies suggest33 represents a promising anti-TB lead that exhibits activity well below toxicity to human monocytic cells.